Dynamics of Islamic Legal Ijtihad Toward the Unification of the Global Hijri Calendar - Taufiqurrahman Kurniawan; Lutfiyatun Nikmah (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2024)
Efforts to realize a globally applicable calendar to unite Muslims in the world have been carried out for a long time. This is done so that there is no longer a difference for Muslims in starting the beginning of the month, thus minimizing conflicts that occur among Muslims.The idea of these efforts not only reaches unification locally, but also internationally. One example of efforts to realize the global Islamic calendar is two calendar system concepts, namely the local hijri calendar with a single global hijri calendar. In this regard, Muslims differ in their views in response to the idea of the concept of unification. using theoretical studies from library research materials including astronomical theories and the results of the thoughts of astronomers or Falak, the decision of the world isbath trial. From the results of this study, it can be concluded that efforts to realize an established Islamic calendar and unite the ummah. The new Indonesian Hisab Rukyat criteria need to be proposed based on Indonesian rukyat data supported by international astronomical criteria based on consideration of the main confounding factors, namely the contrast of light around the sun and twilight light above the horizon. The unification of the Single Global Hijri calendar is needed with significance for reasons including, uniting the world community in the form of an Islamic calendar in terms of the schedule of worship times, so as to realize harmony with one another even in different containers and countries.